Differentiation of mesenchymal stem cells towards lens epithelial stem cells based on three-dimensional bio-printed matrix - Yufan Liu; Zuowei Wang; Tianju Ma; Yi Gao; Wenqian Chen; Zi Ye; Zhaohui Li (Frontiers in Cell and Developmental Biology)
The high risks of traumatic cataract treatments promoted the development of the concept of autologous lens regeneration. Biochemical cues can influence the cellular behavior of stem cells, and in this case, biophysical cues may be the important factors in producing rapid activation of cellular behavior. Here we bio-printed mesenchymal stem cells (MSCs) using a commonly used bioink sodium alginate-gelatin blends, and investigated the induction effect of MSC differentiation towards lens epithelial stem cells (LESCs) under a combination of biochemical cues and biophysical cues. It was found that biochemical cues in the porous three-dimensional (3D) matrix constructed using bioink sodium alginate-gelatin blends for bio-printing did not reduce the cell viability of loaded MSCs in the matrix by scanning electron microscope (SEM) observation and cell viability detection. Loaded MSCs in the matrix were consistently upregulated in the expression of proteins and genes involved in phenotypes and development signaling pathways of LESCs, as detected by polymerase chain reaction (PCR) with the support of biochemical cues. These results indicated that biophysical cues could rapidly activate the cellular behavior of MSCs differentiation, and biochemical cues could continuously induce MSCs differentiation towards LESCs.